International opportunity recognition through international trade intermediary networks in Malaysian SMES - Ahmadian, Sahar (INSInet Publications, 2011)
This paper expatiate the role of International Trade Intermediary (ITI) to International Opportunities Recognition (IOR) in Malaysian Small and Medium sized Enterprises (SMEs). Thirty SMEs were selected for interview. The results illustrate that twenty five SMEs explored international opportunities through their relation with ITIs. This paper also highlighted ten reasons for IOR through ITIs in Malaysian SMEs. The most important reasons are social ties and business networks, familiarity with governmental support, and familiarity with diverse cultures. In addition, government agencies were found the most important intermediary for IOR in Malaysian SMEs.